The Hours Before the Hours: Books of Hours and Almanacs at the Redwood. - Crowley, Patrick (Etc.: The Magazine of the Redwood Library and Athenæum., 2018)
Keywords: dept.lib

John J. Slocum the Collector. - Crowley, Patrick (Etc.: The Magazine of the Redwood Library and Athenæum, 2018)
Keywords: dept.lib

[Two Poems] Translated by Wendeline Hardenberg - Bancquart, Marie-Claire (Absinthe: New European Writing, 2018)
Keywords: dept.lib; ⛔ No DOI found

"Words" Translated by Wendeline Hardenberg - Bancquart, Marie-Claire (One Sentence Poems, 2018)
Keywords: dept.lib

The Matrix and the Machine Translated by Wendeline Hardenberg - Ravalec, Vincent (Asymptote, 2018)
Keywords: dept.lib

Contemporary Art is Internationally Appealing by Vincent Ravalec, translated by Wendeline A. Hardenberg - Gaffey, Marlee (Tupelo Quarterly, 2018)
The challenge was to make appealing something that was not. To transform this godforsaken city, populated by people as indifferent to art as tourists are to the idea of visiting the only historic building—a vague ruin of a castle—in a glamorous destination. After all, what the Guggenheim did for Bilbao could be reproduced […]
Keywords: dept.lib